Effect of nitrogen management on yield and economics of maize (Zea mays L.) in Kandahar region of Afghanistan - Khalili, Azizullah; Dhar, Shiva; Rasrat, Nasir Ahmad; Faiz, Mukhtar Ahmad; Dass, Anchal; Varghese, Eldho (Annals of Agricultural Research, 2016)
A field experiment was conducted at Research Farm of ANASTU, Kandahar, Afghanistan during 2015 to evaluate the effect of nitrogen (N) doses and time of application on yield and economics of maize (Zea mays L.). Treatments consisted four doses of N (0, 120, 180 and 240 kg ha–1) and three N application schedules, ½ dose at sowing (S) + ½ dose at knee high (KH) stage; ½ dose at KH stage + ½ dose at tasseling (T) and ¼ dose at S + ½ dose at KH stage + ¼ dose at T stage and one absolute control (No-N), that were tested in a factorial randomized complete block design (RCBD) replicated thrice. The results revealed that yield attributes, yield and economic returns were higher with 240 kg N ha–1 than others doses of N. These values were also higher when N was applied in three splits as ¼ S + ½ KH + ¼ T. Significantly higher yield attributes, yield and economic returns were obtained when 240 kg N ha–1 was applied in three splits as ¼ dose at sowing + ½ dose at KH stage + ¼ dose at T stage.